Transformational Leadership and Innovation Climate as an Antecedent of Employee Creativity in The Era of The Covid-19 Pandemic - Hayyu Komala Sari; Heru Kurnianto Tjahjono; Sri Handari Wahyuningsih (International Journal of Management Science and Information Technology, 2023)
This research utilized the innovation climate as a mediating variable to examine the impact of transformational leadership style on employee creativity during the COVID-19 pandemic. Respondents in this research were workers of startups. The sample consisted of 129 respondents. The Structural Equation Sampling (SEM) approach was employed using AMOS software to analyze the data. Transformational leadership has a good influence on employee creativity, transformational leadership has a positive effect on the environment of invention, and the atmosphere of innovation has a positive effect on employee creativity, according to this research. Through an innovative atmosphere, transformational leadership has a favorable influence on employee creativity. This research confirms how transformational leadership and an innovation atmosphere are precursors to employee creativity. The consequence of this research is that startup companies must cultivate transformational leadership among their workers and cultivate an innovation-friendly environment so that employees' creativity can be enhanced on occasion.